(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Isradipine is a poorly water soluble antihypertensive drug has low bioavailability. The aim of this study was to formulate and characterize isradipine nanosuspension to enhance the solubility of isradipine and thus its bioavailability. Media milling technique was used for the formulation of nanosuspension. The effects of different important process parameters, i.e. the selection of stirring time, selection of concentration of zirconium beads, stirring speed were investigated by preliminary studies while concentration of stabilizers were optimized by simplex lattice design. Concentration of HPMC E3 LV(X1), Carbopol 934P(X2) and PVP K25(X3) were selected as the independent variables whereas mean particle size (Y1), saturation solubility (Y2) and cumulative percentage drug release (cpr) (Y3) were selected as dependent variables. The optimized batch had 100% w/v of zirconium beads, 0.5%w/v of PVP K25 as stabilizer, 0.1%w/v of isradipine, 15 ml of distilled water and 20 hours of stirring time. The particle size and zeta potential of optimized nanosuspension were 248.6 ± 20 nm and 13.96 ± 5 mV respectively. The size of particles of nanosuspension was measured by particle size analyser and transmission electron microscopy (TEM). Differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FT-IR) analysis indicated that there was no interaction between drug and stabilizers. The saturation solubility and in vitro dissolution rate of isradipine was significantly increased by particle size reduction and which may leads to increase the bio-availability of the Isaradipine. The stability study of the formulation was carried out for a period of 12 months.